Determination of Suitable Drying Model and Energy Efficiency of Mixed Culture Microalgal Biomass by Infrared Drying - Kalender, Mehmet; Yoğurtçu, Hakan (My University, 2025)
In this study, a modeling approach using infrared (IR) drying data of mixed-culture algae, an energy efficiency analysis of the drying process, and some surface proper-ties of the dried product were presented. New model equations derived from com-monly known drying models were applied to experimental data obtained from drying microalgal biomass at various temperatures ranging from 5 to 105 °C. Among these, the DM13 equation, based on the Newton model, best represented the drying behav-ior. The specific moisture extraction rate (SMER) and moisture extraction rate (MER) increased with higher drying temperatures, while, as expected, the specific energy consumption (SEC) decreased. According to the energy efficiency analysis, the IR drying method can be considered suitable for drying microalgal biomass. FT-IR re-sults indicated characteristic green algae peaks attributed to components such as carbohydrates, proteins, and cellulose–fatty acids. Peaks at 2900 cm?¹ and 3386 cm?¹ decreased with increasing drying temperature and disappeared at 105 °C. SEM imag-es showed that microalgal cells experienced shrinkage at 60 °C. Furthermore, while dried microalgal biomass exhibited a porous structure at 50 °C and 60 °C, pores were almost absent at 70 °C and 105 °C.
Keywords: Energy efficiency; infrared drying; derived model equations; mixed culture algae